Participatory design of Short Message Service (SMS) text message to promote mammography among women in Santa Fe, Argentina - Victoria Sánchez Antelo; Melisa Paolino; Paula Frejdkes; Silvina Arrossi (Faculdade de Medicina de Botucatu (Unesp), 2024)
We describe results of the design process of the content of the SMS messages to promote mammography. We conducted four online focus groups with women aged 50 or more (n=14). We used participatory techniques to debate the advantages and disadvantages of different options for the five structural elements of the SMS message. Our results showed that women argued that the opening line should provide clear information about the topic of the SMS message. SMS messages should include the woman's name, information about who and how to get a mammogram and use a health institution as a sender. The closing line should encourage women to get a mammogram. A personalized SMS could be a good way of inviting women to perform the mammography. The content must be carefully designed to provide clear information about how to schedule an appointment.